2012
DOI: 10.1063/1.4718726
|View full text |Cite
|
Sign up to set email alerts
|

Aeroacoustic power generated by multiple compact axisymmetric cavities: Effect of hydrodynamic interference on the sound production

Abstract: Aeroacoustic sound generation due to self-sustained oscillations by a series of compact axisymmetric cavities exposed to a grazing flow is studied both experimentally and numerically. The driving feedback is produced by the velocity fluctuations resulting from a coupling of vortex sheddings at the upstream cavity edges with acoustic standing waves in the coaxial pipe. When the cavities are separated sufficiently from each other, the whistling behavior of the complete system can be determined from the individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In most practical situations, the self-sustained oscillations, tuned by the cavity volume or depth, exhibit maximum amplitudes in the low Mach number range. The third type acoustic resonance has been recently investigated by Nakiboglu et al [27][28][29] They explored the whistling of corrugated pipes and compact axisymmetric cavities, where the acoustic feedback is provided possibly by the longitudinal standing waves inside the coaxial pipes.…”
Section: Introductionmentioning
confidence: 99%
“…In most practical situations, the self-sustained oscillations, tuned by the cavity volume or depth, exhibit maximum amplitudes in the low Mach number range. The third type acoustic resonance has been recently investigated by Nakiboglu et al [27][28][29] They explored the whistling of corrugated pipes and compact axisymmetric cavities, where the acoustic feedback is provided possibly by the longitudinal standing waves inside the coaxial pipes.…”
Section: Introductionmentioning
confidence: 99%
“…There are two possible ways of determining this function of Sr.. The first way is the numerical approach described in Refs., 11,13,15 which predicts A(Sr) with a factor of 2 accuracy. The second way, used here, is a simpler engineering approach: we estimate the shape of A(Sr) empirically.…”
Section: Model For A(sr)mentioning
confidence: 98%
“…11,13,15 The low-amplitude asymptotic behavior demonstrates that the time averaged power, P src , is proportional to ρ 0 |u ′ | 2 U cp S cp at low amplitudes |u ′ |/U cp ≪ 1.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, they proposed a mathematical model for predicting the whistling noise; the results showed that the sound generation mainly occurred in an area around pressure nodes of standing waves, and this outcome contradicts the experimental results obtained by Kristiansen and Wiik. 6 Furthermore, Nakibog˘lu and colleagues [7][8][9][10] carried out a set of numerical and experimental investigations to understand the effect of geometry parameters on aero-acoustical interaction of the corrugated pipe. Recently, Lacombe et al 11 carried out a numerical study on the linear response of a single orifice by using computational fluid dynamics (CFD) software.…”
Section: Introductionmentioning
confidence: 99%